Implementasi Metode Template Matching untuk Mengenali Nilai Angka pada Citra Uang Kertas yang Dipindai - Muria Naharul Hudan Najihul Ulum; Tibyani Tibyani; Sigit Adinugroho (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Money is a valuable tools that are needed by all of the people for payment. Moreover, when people knowing about the money, the computer have limited ability to read the image of money. Computer is an electronic tool that used to receive and store the data, processing that and produce the output that already saved in the memory. The case of computer or robot that cannot notes the value of money because of the limited access in introducing the data, made the researcher provide a solutions from that problem to support the application of money which called template matching. A matching template is an input image that matches the linkeness of the test image. Based on that template matching method is designed for the data training and introduction of the data. A series of test was used in diagnostic to calculate the accuracy. So the average result will be 91% from all of the calculation of diagnostic test. Therefore, the error will state in front of money.